The role of cholesterol metabolism and cholesterol transport in carcinogenesis: a review of scientific findings, relevant to future cancer therapeutics - Cruz, Pedro M.; Mo, Huanbiao; McConathy, Walter; Sabnis, Nirupama A.; Lacko, Andras G. (Frontiers in Pharmacology, 2013)
While the unique metabolic activities of malignant tissues as potential targets for cancer therapeutics has been the subject of several recent reviews, the role of cholesterol metabolism in this context is yet to be fully explored. Cholesterol is an essential component of mammalian cell membranes as well as a precursor of bile acids and steroid hormones. The hypothesis that cancer cells need excess cholesterol and intermediates of the cholesterol biosynthesis pathway to maintain a high level of proliferation is well accepted, however the mechanisms by which malignant cells and tissues reprogram cholesterol synthesis, uptake and efflux are yet to be fully elucidated as potential therapeutic targets. High and low density plasma lipoproteins, area the likely major suppliers of cholesterol to cancer cells and tumors, potentially via receptor mediated mechanisms. This review is primarily focused on the role(s) of lipoproteins in carcinogenesis, and their future roles as drug delivery vehicles for targeted cancer chemotherapy.